The effects of different doses of inhaled bacteriophage therapy for Pseudomonas aeruginosa pulmonary infections in mice. (July 2022) - Chang, Rachel Yoon Kyung; Chow, Michael Y.T.; Wang, Yuncheng; Liu, Chengxi; Hong, Qixuan; Morales, Sandra; McLachlan, Andrew J.; Kutter, Elizabeth; Li, Jian; Chan, Hak-Kim
Abstract: Objectives: Inhaled phage therapy has been revisited as a potential treatment option for respiratory infections caused by multidrug-resistant Pseudomonas aeruginosa ; however, there is a distinct gap in understanding the dose–response effect. The aim of this study was to investigate the dose–response effect of Pseudomonas -targeting phage PEV31 delivered by the pulmonary route in a mouse lung infection model. Methods: Neutropenic BALB/c mice were infected with multidrug-resistant P. aeruginosa (2 × 10 4  colony-forming units) through the intratracheal route and then treated with PEV31 at three different doses of 7.5 × 10 4 (Group A), 5 × 10 6 (Group B), and 5 × 10 8 (Group C) plaque-forming units, or phosphate-buffered saline at 2 hours postinoculation. Mice ( n  = 5–7) were euthanized at 2 hours and 24 hours postinfection, and lungs, kidneys, spleen, liver, bronchoalveolar lavage fluid, and blood were collected for bacteria and phage enumeration. Results: At 24 hours postinfection, all phage-treated groups exhibited a significant reduction in pulmonary bacterial load by 1.3–1.9 log10, independent of the delivered phage dose. The extent of phage replication was negatively correlated with the dose administered, with log10 titre increases of 6.2, 2.7, and 9 for Groups A, B, and C, respectively. Phage-resistant bacterial subpopulations in the lung homogenate samples harvested at 24 hours postinfection increased with the treatment dose (i.e. 30%, 74%, and 91% in respective Groups A–C). However, the mutants showed increased susceptibility to ciprofloxacin, impaired twitching motility, and reduced blue-green pigment production. The expression of the inflammatory cytokines (IL-1ß and IL-6, and TNF-α) was suppressed with increasing PEV31 treatment dose. Discussion: This study provides the dose–response effect of inhaled phage therapy that may guide dose selection for treating P. aeruginosa respiratory infections in humans.